2010
DOI: 10.1099/ijs.0.016303-0
|View full text |Cite
|
Sign up to set email alerts
|

Rhodotorula rosulata sp. nov., Rhodotorula silvestris sp. nov. and Rhodotorula straminea sp. nov., novel myo-inositol-assimilating yeast species in the Microbotryomycetes

Abstract: A distinguishing feature of the majority of the tremellomycetous yeasts is their ability to utilize a cyclitol, myoinositol, as sole source of carbon and energy. This characteristic, which, as a rule, is not shared by ascomycetous yeasts and by basidiomycetous yeasts of other classes, represents a fundamental key in yeast identification. Specifically, inositol assimilation is a criterion used to distinguish between anamorphic yeasts of the genera Cryptococcus Vuillemin and Rhodotorula Harrison (Kurtzman & Fell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…They were also found to inhabit densely vegetated soils, including forest, podzolic and sod-podzolic soils, in regions with tropical, temperate and cold climates (Vishniac 2006; Fonseca et al 2011; Sugita 2011). Likewise, all yeast species found in this study, were also currently found as a part of yeast diversity in soil ecosystems (Golubev 1984; Maksimova and Cherov 2003; Wuczkowski and Prillinger 2004; Botha 2006; Golubtsova et al 2006; Lynch and Thorn 2006; Vishniac 2006; Golubev and Scorzetti 2010; Mestre et al 2011; Yurkov et al 2011, 2012, 2016; Buzzini et al 2012). As previously reported, soil yeasts can contribute to essential soil ecological processes, i.e.…”
Section: Discussionsupporting
confidence: 74%
“…They were also found to inhabit densely vegetated soils, including forest, podzolic and sod-podzolic soils, in regions with tropical, temperate and cold climates (Vishniac 2006; Fonseca et al 2011; Sugita 2011). Likewise, all yeast species found in this study, were also currently found as a part of yeast diversity in soil ecosystems (Golubev 1984; Maksimova and Cherov 2003; Wuczkowski and Prillinger 2004; Botha 2006; Golubtsova et al 2006; Lynch and Thorn 2006; Vishniac 2006; Golubev and Scorzetti 2010; Mestre et al 2011; Yurkov et al 2011, 2012, 2016; Buzzini et al 2012). As previously reported, soil yeasts can contribute to essential soil ecological processes, i.e.…”
Section: Discussionsupporting
confidence: 74%
“…Hannaella coprosmae , a basidiomycetous yeast, has been found on the phylloplane of plant leaves (Li et al . 2020 ), and Oberwinklerozyma straminea (or Rhodotorula straminea ) is a yeast found in dead needle litter of Picea abies L. and Pinus sylvestris L. (Golubev and Scorzetti 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The species belonging to the genus Rhodotorula typically do not assimilate myoinositol. It should be noted that such differentiation is becoming less distinct: there are more and more reports on inositol-positive Rhodotorula species (Golubev & Scorzetti, 2010).We found that the Rhodotorula No.BY1109 was positive for myoinositol assimilation. An rDNA gene sequence analysis and a comparison of its phenotypic properties revealed that the isolates might constitute novel anamorphic species in the Rhodotorula for which the names Rhodotorula langang sp are proposed.…”
Section: Discussionmentioning
confidence: 49%